Analisis Diskriminan Melalui Metode Fisher Terhadap Kemampuan Siswa Dalam Menguasai Materi Bangun Ruang Pada Kelas Viii Smp Negeri 1 Banda Aceh Tahun Pelajaran 2013/2014 - Khairul Umam; Yuhasriati Yuhasriati; Nadya Nadya (Universitas Syiah Kuala, 2015)
One factor that is often happened is the learning objectives are difficult to achieve, because students often make mistakes in understanding the concepts and performing calculations. One way that teachers can do to minimize these errors is to classify between students who have been able to master the material and students who have not been able to master the material. Discriminant analysis is one way to facilitate the grouping of students according to their ability to master the material, by using the method of Fisher. The purpose of this study was determining how the percentage of students who have mastered the material prism and pyramid, getting the discriminant function of the prism and pyramid mastery of the material, and determining the factors that cause students difficult to understand the material prism and pyramid. The study population was the entire eighth grade students of SMP Negeri 1 Banda Aceh while the sample were students of class VIII-8 to 30 students. Based on the research that has been done using the fisher discriminant analysis method, 33.3% of students have mastered the material geometry and 66.6% of students have not mastered the material prism and pyramid. It means that from 30 students only 10 students were able to master the material well-prism and pyramid. End function that is formed is Y1 = 5,487X1 + 3,373X2 - 4,822X3 + 5,936X4 + 1,544X5 - 2,108X6 and Y2 = 5,486X1 + 3,373X2 - 4,823X3 + 5,937X4 + 1,544X5 - 2,107X6.